An Iconic Image: Henry Ward Beecher in Puck Magazine. (September 2018) - Marks, Patricia
Henry Ward Beecher, the influential pastor of Plymouth Church in Brooklyn until his death in 1887, became an iconic figure in Puck magazine during its first decade. Beecher, who was involved in the Tilton marital scandal, was satirized in word and graphics by editor and cartoonist Joseph Keppler for both his womanizing and his politics. A study of Puck 's response to Beecher from 1877 to 1887 exemplifies the magazine's crusade against dishonesty and attempt to safeguard public morals as it followed in the steps of its mascot Puck, proclaiming "What Fools These Mortals Be!"